2014
DOI: 10.1158/0008-5472.can-13-1713
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 in Macrophage: Contributions to Cigarette Smoke–Induced Lung Cancer

Abstract: Expression of the pro-oncogenic mucin MUC1 is elevated by inflammation in airway epithelial cells, but the contributions of MUC1 to the development of lung cancer are uncertain. In this study, we developed our finding that cigarette smoke (CS) increases Muc1 expression in lung macrophages, where we hypothesized it might contribute to CS-induced transformation of bronchial epithelial cells. In human macrophages, CS extract (CSE) strongly induced MUC1 expression through a mechanism involving the nuclear receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 34 publications
(58 reference statements)
2
26
0
Order By: Relevance
“…KL-6, a complex carbohydrate antigen of human MUC1, was elevated in AMs and regenerating type 2 pneumocytes in patients with idiopathic interstitial pneumonia (30). A causal effect of cigarette smoke on increased expression of MUC1/Muc1 by mAMs in vivo and human macrophage cell lines was reported (11). The results of the current study are consistent with previous in vivo data demonstrating that Pa lung infection up-regulated mouse Muc1 levels in lung tissue and increased shed Muc1-EC levels in bronchoalveolar lavage fluid (18).…”
Section: Muc1/muc1 Deficiency Enhances Ros Production and Tnf-a Releasupporting
confidence: 92%
See 2 more Smart Citations
“…KL-6, a complex carbohydrate antigen of human MUC1, was elevated in AMs and regenerating type 2 pneumocytes in patients with idiopathic interstitial pneumonia (30). A causal effect of cigarette smoke on increased expression of MUC1/Muc1 by mAMs in vivo and human macrophage cell lines was reported (11). The results of the current study are consistent with previous in vivo data demonstrating that Pa lung infection up-regulated mouse Muc1 levels in lung tissue and increased shed Muc1-EC levels in bronchoalveolar lavage fluid (18).…”
Section: Muc1/muc1 Deficiency Enhances Ros Production and Tnf-a Releasupporting
confidence: 92%
“…Moreover, M0 THP-MUC1 shRNA cells had increased TNF-a release in response to Pa compared with M0 THP-control shRNA cells ( Figure 6C). In summary, the collective results of this study indicate that: (1) Increased expression of MUC1 by hAMs has been shown to be associated with the histopathogenesis of some lung diseases (11,30). KL-6, a complex carbohydrate antigen of human MUC1, was elevated in AMs and regenerating type 2 pneumocytes in patients with idiopathic interstitial pneumonia (30).…”
Section: Muc1/muc1 Deficiency Enhances Ros Production and Tnf-a Releamentioning
confidence: 70%
See 1 more Smart Citation
“…Two micrograms of RNA were used as a template for cDNA synthesis with a reverse transcription kit (Promega). An equal volume of cDNA product was subjected to reverse transcription-polymerase chain reaction (RT-PCR) analysis according to our previous study (21). The following primers were used in the PCR reactions: MUC1, forward primer 5′-ACAATTGACTCTGGCCTTCCG-3′ and reverse primer 5′-TGGG TTTGT GTA AG AGAGGCT-3′; β-actin, forward primer: 5′-CCA GCCTTCCTTCCTGGGCAT-3′ and reverse primer 5′-AGGAGCAATGATCT TGATCTTCATT-3′; Catalase, forward primer 5′-GGGAGAAGGCAAATCT GTGA-3′ and reverse primer 5′-GCACA TCTA GCAC AGGA GAAT-3′.…”
Section: Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%
“…We recently found that chronic cigarette smoke exposure induces persistent MUC1 overexpression in human lung bronchial epithelial cells, which facilitates cigarette smoke-induced cell transformation through EGFR-mediated cell survival signaling (20). In addition, MUC1 mediates cigarette smoke extract-induced TNFα secretion from macrophages to engender a lung cancer-prone microenvironment (21), suggesting that MUC1 functions in both lung macrophages and bronchial epithelial cells for lung cancer development. However, direct evidence for the role and mechanisms of MUC1 in acquired chemoresistance in lung cancer is lacking.…”
Section: Introductionmentioning
confidence: 99%